Renaissance en barok : van het Plantin-Moretushuis tot het Rubenshuis - Heirman, Michiel, 1951-; Tijs, Rutger J., 1949- (Tielt : Lannoo, 2008)
Brugge, Mechelen, Luik, Zoutleeuw, Brugge, Antwerpen, Gent, Heverlee, Doornik, Bouvignies, Verune, Oudenaarde, Scherpenheuvel, Elsenen, Aalst, Nivove, Machelen, Modave, Grimbergen, Averbode, Puurs, Kortenbos
Keywords: Barok; Renaissance